Teman Usaha Rakyat: Development Of A Strategy To Accelerate Economic Escalation And Umkm Class Up In Banyuwangi - Rosyidah, Elok; Irfan, Mohamad; Maskunatin, Iva; Tri Lestari, Sinta; NurRohman, Alfian (International Publisher (YAPENBI), 2022)
Banyuwangi Regency is one of the affected districts, in terms of the economy experiencing a decline due to the Coronavirus Pandemic (Covid-19). The decline in economic growth in Banyuwangi Regency in 2020 is -0.03%. One of the sectors that can be used as a focus for improvement is UMKM. Teman Usaha Rakyat will provide assistance to the perpetrators UMKM overall. Such as improving product quality, marketing innovation, encouraging UMKM go-digital order, permit processing, certificates, good narrative writing, simple design and more. The purpose of the study is to find out whether the strategy of the Teman Usaha Rakyat program already able to raise the class UMKM in Banyuwangi and provide recommendations for program improvement by Amplification Plan Monitoring and Evaluation of mentoring activities for perpetrators UMKM upgrading in Banyuwangi. This research uses the method Research and Development (RnD). The results of the statistical test of the mean difference before and after treatment in the experimental group (perpetrators UMKM) with the help of the program SPSS 19 the mean value of the pre-assistance questionnaire was obtained = 65.66 and post-mentoring questionnaires = 82.00. This means that there is a positive and significant influence on the implementation of the Teman Usaha Rakyat program.